Congenital megaesophagus in Yorkshire: a case report (Research, Society and Development, 2022)
Congenital megaesophagus is characterized by a general and diffuse disorder resulting from a disorder in motility, making the organ inefficient and congenital dilatation in several problems of recurrence in motility. Its strategy is not fully elucidated, and the main suspicion is related to clinical systems in young animals. The aim of this study was to report the occurrence of congenital megaesophagus in a Yorkshire Terrier and its prognostic evolution through prescribed therapy. A 3-month-old male dog with a history of post-food and water regurgitation was treated. Hematological, biochemical and radiographic examinations were requested. Hematological examination confirmed a suspicion of megaes radiographic examinations and hematological examinations to be ruled out the possibility of systemic or problems. The picture was based on the clinical picture presented, such as the use of food, as well as the treatment in an upright position and without use. The patient improved from the multimodal therapy performed.